2008
DOI: 10.1103/physrevb.78.075435
|View full text |Cite
|
Sign up to set email alerts
|

Band structure engineering of graphene by strain: First-principles calculations

Abstract: We have investigated the electronic structure of graphene under different planar strain distributions using the first-principles pseudopotential plane-wave method and the tight-binding approach. We found that graphene with a symmetrical strain distribution is always a zero band-gap semiconductor and its pseudogap decreases linearly with the strain strength in the elastic regime. However, asymmetrical strain distributions in graphene result in opening of band gaps at the Fermi level. For the graphene with a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
365
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 604 publications
(398 citation statements)
references
References 30 publications
30
365
1
2
Order By: Relevance
“…The asymmetry between the conduction band () and the valence band (), which is especially pronounced in the vicinity of the point, which is attributed to the non-zero overlap parameter . However, the electronic band structure of graphene can be simply altered by applying electric field [6,5761] or providing substrates [62,63], and precisely engineered by introducing disorders into the hexagonal lattice [6468], which will be discussed in detail in later sections.…”
Section: The Structure Of Graphenementioning
confidence: 99%
“…The asymmetry between the conduction band () and the valence band (), which is especially pronounced in the vicinity of the point, which is attributed to the non-zero overlap parameter . However, the electronic band structure of graphene can be simply altered by applying electric field [6,5761] or providing substrates [62,63], and precisely engineered by introducing disorders into the hexagonal lattice [6468], which will be discussed in detail in later sections.…”
Section: The Structure Of Graphenementioning
confidence: 99%
“…In particular, recent ab initio calculations [19][20][21][22] as well as experiments 23 have demonstrated that graphene can sustain elastic deformations as large as 20%. The possibility of a straininduced semimetal-to-semiconductor transition, with the opening of a gap, has been therefore studied [24][25][26][27] . It turns out that this critically depends on the direction of applied strain, as is also confirmed by studies of the strain effect on the optical conductivity of graphene [28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…[63] Figure 4(e)-4(g), in turn, shows the band structures of single-layer h-BN when the critical uni-axial strain is applied along the zigzag direction, along the armchair direction, and bi-axially. Very different from graphene, which has been shown that mechanical strain has very little effect on the band structure of large-area graphene, [64,65] the band gap of h-BN decreases dramatically with increasing tensile strain. A summary of the band gap as a function of different values of the strain in the three typical directions is given in Figure 4(c).…”
mentioning
confidence: 99%